Effects of combined temperature and salinity on growth and fatty acid content of two Korean isolates of Akashiwo sanguinea (Dinophyceae) - Ji Yeon Kim; Joo-Hwan Kim; Zhun Li; Kyong Ha Han; Minjae Kim; Minseok Jeong; Kyun-Woo Lee; Ji Hoon Lee; Joo Yeon Youn; Pung-Guk Jang; Kyungsoon Shin; Da Bin Choi; et al. (Scientific Reports)
Abstract Two Korean strains of Akashiwo sanguinea (LMBE-V203 and LMBE-V287) were established, and their morphologies and molecular phylogenies were examined. In addition, the effects of combined temperature and salinity on their growth and fatty acid contents were examined to evaluate the value as potential source for commercial application. Morphological observations indicated that there were no critical differences in the morphologies of both isolates, and molecular phylogeny based on LSU rRNA gene sequences revealed that the two isolates are nested within ribotype A of A. sanguinea. The two isolates exhibited different growth responses to combined temperature and salinity conditions, because of possibly the differences in sampling locations characterized by of different environmental conditions. At the optimal temperature and salinity, the maximum cell concentration was approximately three times higher in culture of LMBE-V287 than in culture of LMBE-V203, and the growth rate in the culture of LMBE-V287 was also higher than that in the culture of LMBE-V203. The optimal conditions to maximize biomass for batch cultures of Korean isolates of A. sanguinea (ribotype A) were a temperature of 20 °C and a salinity of 35. Cultures of two isolates had similar fatty acid compositions, and both isolates had a moderate content of EPA plus DHA, compared to other microalgal species. Therefore, the two Korean isolates of A. sanguinea (ribotype A) can be candidates for the commercial production of EPA plus DHA. There were differences in the fatty acid contents between the cultures of two isolates exposed to combined temperature and salinity conditions. The monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) of LMBE-V203 at the same salinity increased with decreasing temperature and the saturated fatty acids (SFAs) under same salinity level increased with increasing temperature, whereas no clear tendency for the SFAs and PUFAs of LMBE-V287 was found. This result indicates that the MUFAs and PUFAs of strain LMBE-V203 can be modulated by controlling temperature.